2021
DOI: 10.47206/ijsc.v1i1.81
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Training Recommendations to Maximize Muscle Hypertrophy in an Athletic Population: Position Stand of the IUSCA

Abstract: Hypertrophy can be operationally defined as an increase in the axial cross-sectional area of a muscle fiber or whole muscle, and is due to increases in the size of pre-existing muscle fibers. Hypertrophy is a desired outcome in many sports. For some athletes, muscular bulk and, conceivably, the accompanying increase in strength/power, are desirable attributes for optimal performance. Moreover, bodybuilders and other physique athletes are judged in part on their muscular size, with placings predicated on the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
65
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 219 publications
(276 reference statements)
8
65
0
5
Order By: Relevance
“…Although some guidelines suggest the use of high and moderate loads to development maximal strength and muscle hypertrophy, several studies showed increases in maximal strength and muscle hypertrophy after resistance training with low loads (i.e., <60% 1RM) [ 13 , 14 , 15 , 16 , 17 ]. These studies are in line with recent guidelines indicating that the athletic population may achieve comparable muscle hypertrophy across a wide spectrum of loading zones [ 18 ]. However, meta-analysis data provided no differences in muscle hypertrophy between high and low loads (≥80% 1RM, or ≤8RM vs. <60% 1RM, or >15RM), moderate and low loads (60–79% 1RM, or 9–15RM vs. <60% 1RM, or >15RM), or high and moderate loads (≥80% 1RM, or ≤8RM vs. 60–79% 1RM, or 9–15RM) during resistance training performed until volitional failure in healthy adults [ 19 ].…”
Section: Introductionsupporting
confidence: 89%
“…Although some guidelines suggest the use of high and moderate loads to development maximal strength and muscle hypertrophy, several studies showed increases in maximal strength and muscle hypertrophy after resistance training with low loads (i.e., <60% 1RM) [ 13 , 14 , 15 , 16 , 17 ]. These studies are in line with recent guidelines indicating that the athletic population may achieve comparable muscle hypertrophy across a wide spectrum of loading zones [ 18 ]. However, meta-analysis data provided no differences in muscle hypertrophy between high and low loads (≥80% 1RM, or ≤8RM vs. <60% 1RM, or >15RM), moderate and low loads (60–79% 1RM, or 9–15RM vs. <60% 1RM, or >15RM), or high and moderate loads (≥80% 1RM, or ≤8RM vs. 60–79% 1RM, or 9–15RM) during resistance training performed until volitional failure in healthy adults [ 19 ].…”
Section: Introductionsupporting
confidence: 89%
“…Weight resistance training (RT) has been proven as an important tool to improve performance in different sports disciplines [ 1 , 2 , 3 , 4 ]. In addition, RT is also a key factor to improve body composition in physically active population [ 5 , 6 ], health condition in the general population [ 7 , 8 ], and even as preventive and palliative treatment in many metabolic and neurodegenerative diseases [ 9 , 10 ]. The magnitude of the effect produced by RT will depend on the manipulation of the so-called acute training variables, especially the relative load, volume, and type of exercises [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that increases in muscular strength and muscle size with resistance training favour higher training volumes [ 27 , 28 , 29 , 30 ]. Given that the findings presented herein demonstrate an increase in muscular endurance and, therefore, training volume, it might be that using an external focus of attention over the long term also enhances outcomes such as muscular strength and hypertrophy.…”
Section: Discussionmentioning
confidence: 99%